ANALYSIS OF FINANCIAL PERFORMANCE IN ARTHA PRIMA COOPERATIVES IN ENOK SUBDISTRICT REGIONAL INDRAGIRI DISTRICT - Evi Andri Yani; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the financial performance of the Village Transfer Cooperative District Enok District Indragiri Hilir in 2014 to 2018 by using the ratio of liquidity, solvency and profitability. This type of research conducted in the form of secondary data which data from the financial statements. Data collection techniques used were the method of observation, interviews and documentation methods. The data analysis technique used is by collecting and grouping financial statement data and evaluating financial performance. Based on the results of the analysis of the financial data of the Artha Prima Cooperative in Pengransfer Village, Enok Subdistrict, Indragiri Regency, it was concluded that the level of liquidity in 2014-2018 in terms of the current ratio gets bad results (bad) and cash ratio gets bad results (bad). The level of solvency in 2014-2018 in terms of DAR and DER showed very good results. The level of profitability in 2014-2018 in terms of ROA, ROE and NPM showed good results. Judging from the calculation of the analysis of liquidity ratios, solvency and profitability, it is said that the financial performance of the Artha Prima Cooperative, Desa Pengransfer, Enok District needs to be improved so that it can be even better in the future.Keywords: liquidity, solvency and rentability